(2R)-4-[(9H-Fluoren-9-ylmethoxy)carbonyl]-2-methylpiperazin-1-ium chloride - Ertan, Anne (International Union of Crystallography, 2011)
The synthesis of the title salt, C(20)H(23)N(2)O(2) (+)·Cl(−), was carried out with a precursor of known absolute configuration (R) and the X-ray analysis confirmed that the product retained the absolute configuration. In the crystal, the dominant packing motif is a chain running along [010] generated by N—H⋯Cl hydrogen bonding. C—H⋯O and C—H⋯Cl interactions are also observed.